Etnomatematika: Eksplorasi Amak Lampisan Mandailing dalam Pembelajaran Matematika - Hasibuan, Adil Halomoan; Suparni, Suparni (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2024)
The decline in cultural understanding among society is something that must be taken seriously and requires ongoing study, because culture is one of the distinctive characteristics of a nation. Linking the surrounding culture with learning is one step to preserve and maintain this culture for future generations. Amak lampisan Mandailing is a typical woven mat from the Mandailing Tribe which has elements of mathematical concepts in it. The ethnomathematics studied are mathematical concepts related to learning material at SMP/MTs and equivalent schools. This research uses exploratory research with an ethnographic approach to study the relationship between culture and learning materials. explore the shapes and patterns of amaklampisan. The aim of this research is to bring out cultural wisdom in mathematics learning so that it can motivate and influence students' learning achievement. This type of research is exploratory qualitative research about Amak Lampisan Mandailing. Based on the results of this research, Mandailing lampisan amak is related to material in mathematics such as rectangles, congruence and similarity, arithmetic sequences and series, social arithmetic.